Too Much of a Good Thing: Accelerated Growth and Crime - Rodrigo R. Soares; Danilo Souza (Institute of Labor Economics (IZA), 2023)
We document that oil-producing areas of Brazil experienced increases in crime during the period of increased economic growth driven by the 2000s oil boom. This challenges the understanding that the impact of income shocks on crime is driven primarily by the legal status of the market in question. Offshore oil production, refining, and distribution in Brazil are concentrated in large firms, without scope for income contestability. We show that various equilibrium effects of the shock – such as increased inequality, urbanization, illegal goods presence, and deterioration in public goods provision – are likely to have contributed to the increase in crime.
Keywords: H75; K42; Q34; 330; crime; oil; income; Brazil